2014
DOI: 10.1186/2193-1801-3-414
|View full text |Cite
|
Sign up to set email alerts
|

Comments on the mechanisms of action of radiation protective agents: basis components and their polyvalence

Mikhail V Vasin

Abstract: PurposeThese comments suggest a division of radiation protective agents on the grounds of their mechanism of action that increase the radio resistance of an organism.ConclusionGiven below is the division of radiation protective agents on the basis of their mechanism of action into 3 groups: 1) Radiation protective agents, with the implementation of radiation protective action taking place at the cellular level in the course of rapidly proceeding radiation-chemical reactions. At the same time, when the ionizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 149 publications
0
15
0
1
Order By: Relevance
“…As an example, hypoxia is an important mechanism for tumor radioresistance in hypofractionated radiotherapy, which must be considered in the treatment planning process [112] , while an agent that could temporarily create hypoxic condition in the normal tissue may have radioprotective effect [113] .…”
Section: Ra Its Categoris and Mechanisms Of Functionmentioning
confidence: 99%
“…As an example, hypoxia is an important mechanism for tumor radioresistance in hypofractionated radiotherapy, which must be considered in the treatment planning process [112] , while an agent that could temporarily create hypoxic condition in the normal tissue may have radioprotective effect [113] .…”
Section: Ra Its Categoris and Mechanisms Of Functionmentioning
confidence: 99%
“…Also, on day 8 after irradiation, BP-C2, administered to C57BL/6 mice 24 h after 7.0 Gy of irradiation, improved animal survival by 40% and mean survival time (MST) by 1.5 days. This type of pattern is common for radiomitigators, which in general have a low DRF and are efficient mostly in the mid-lethal range of radiation doses (Vasin 2014;Singh et al 2014a;Rosen et al 2014). Such agents exert a systemic effect, accelerating recovery of radiosensitive tissues after exposure to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there remains an unmet medical need for radioprotective and mitigative agents. Phenolic compounds (rosmarinic acid (Xu et al 2016), lycopene (Gajowik and Dobrzynska 2014) and flavonoids (Grebeniuk et al 2013;Vasin 2014)) are reported to exert radioprotective effects through various mechanisms. BP-C2 is a novel lignin-derived polyphenolic composition with ammonium molybdate.…”
Section: Introductionmentioning
confidence: 99%
“…O gasto energético do consenso por prova de trabalho é ecologicamente inaceitável. Outros algoritmos baseados em prova procuram mitigar o excesso de gasto energético e as limitações de desempenho presentes na prova de trabalho [Vasin 2014, Schwartz et al 2014, Kiayias et al 2017. Uma breve explicação dos algoritmos mais conhecidos é mostrada a seguir:…”
Section: Consenso Probabilístico: Protocolos Baseados Em Provasunclassified